Holding Power of Orthopaedic Screws in Bovine Femoral Heads - Wilson, D. G.; Ulm, M. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Femoral capital physeal fractures have been successfully repaired using 7.0 mm cannulated screws. The holding power of 7.0 mm cannulated screws was compared to the holding power of 5.5 mm cortical screws and 6.5 mm cancellous screws using paired bovine femoral heads. The 7.0 mm cannulated screw’s holding power was superior to the 6.5 mm cancellous screw and similar to that of the 5.5 mm cortical screw.When placed in the bovine femoral head, 7.0 mm cannulated screws have holding power greater than 6.5 mm cancellous screws and similar to 5.5 mm cortical screws.
Keywords: Femoral capital physeal fractures; cannulated screw; cattle